Pelatihan Perhitungan Pajak Restoran di Kota Lamongan - Rina Sulistyowati; Yulis Saidah; Dinasti Aulia Hakim (Jurnal Pengabdian Masyarakat Nusantara, 2020)
Restaurant Tax is one of the Programs from the Directorate General of Taxes which has the objective of being a tax on the consumption of goods and services within the Customs Area which is imposed in stages in each line of production and distribution. VAT is an indirect tax because the payment or collection of the tax is deposited by another party who is not the taxpayer. Tax Servants (Tax Lecturers) have the task of assisting taxpayers (RM. Bebek general and RM. Kaliotic) related to online tax reporting techniques or e-feliing. The result of this PKM training is that tax servants can understand the concept of taxation and how to calculate VAT on consumer products and services. So as to assist tax servants in carrying out assistance to partners in 2020.